Magic Laws and The Functions of Fantasy in A Fantasy Novel - Gavra Cindy Amelis (Universitas Pendidikan Indonesia (UPI), 2013)
Martin (2007) argues that limitation is one component which makes Harry Potter story work. Limitation is a part of magic laws that were investigated in this research, along with the functions of the fantasy and how these elements work to construct a story in The Lightning Thief, a fantasy novel written by Riordan (2005). Magic Law theory as proposed by Nikolajeva (1988) and Tolkien’s function of fantasy (1966) were used as the framework theory. Textual analysis was used to find out the answers to the research questions. This research finds that the kinds of magic laws used in The Lightning Thief are limitation and consistency while recovery and escape are two functions of fantasy served in the novel. The magic laws and functions of fantasy construct the story to be interesting, believable, and related to human life by creating the element of wonder, creating the element of surprise, maintaining the balance between primary and secondary world, composing the inner logic of the story, and conveying some interesting issues.. Keywords: The Lightning Thief, Fantasy Novel, Magic Laws, Functions of Fantasy